Do prospector firms pay more dividends in times of high policy uncertainty? - Viet Anh Hoang; Thanh Huong Nguyen; My Hanh Nguyen; Ba Thanh Truong (Cogent Business & Management, 2024)
This research aims to explore the nexus between business strategy and dividend payments. Utilizing a dataset encompassing U.S.-listed firms spanning the period from 1995 to 2018, our analysis reveals that firms employing prospector strategies exhibit a higher propensity for dividend payments compared to defender firms. Our findings persist even when accounting for firm fixed effects, employing an alternative subsample methodology, and demonstrating resilience to endogeneity and Propensity Score Matching (PSM) analysis. We also document that agency conflict issues related to free cash flow in prospector firms, stemming from overinvestment and capital expenditure reduction, contribute to an escalation in dividend payouts relative to defender firms. Finally, the prospector-dividend payment association is more pronounced in the context of weaker firm-level information and governance environments and during periods characterized by high policy uncertainty. Overall, our study fills a crucial gap in the literature on the complexities of dividend decisions within the context of different strategic orientations.
Keywords: 650; business strategy; dividend payments; overinvestment; capital expenditure; information and governance environments; policy uncertainty